Knowledge, attitudes, and practices of oral and maxillofacial surgeons towards the use of artificial intelligence in clinical practice and training: a cross-sectional study - Quah, Bernadette; Yong, Chee Weng; Chen, Matthias Wei Jin; Lai, Clement Wei Ming; Islam, Intekhab (Frontiers in Oral Health, 2025)
AimThis study aimed to evaluate the knowledge, attitudes, and practices of oral and maxillofacial surgery (OMS) clinicians and trainees relating to the use of artificial intelligence (AI) within OMS practice and training.MethodsA cross-sectional survey study was conducted with OMS specialists and trainees in Singapore regarding their views on AI in OMS. The survey comprised 25 questions over five sections, and was distributed via an online survey platform.Results48 participants completed the survey, including 37 specialists and 11 trainees. 60.4% did not report a good understanding of AI, 52.1% were not aware of the uses of AI in OMS, and 81.3% had not had any form of AI-related training. Most felt that AI could be beneficial for diagnosis and treatment planning (72.9%) and enhancing patient outcomes (75.0%), and should be incorporated into OMS training (68.8%). While there were no differences between genders, younger participants tended towards more positive attitudes (p < 0.05). Participants cited concerns about inaccurate diagnoses or plans (77.1%), overdependence (70.8%), privacy/security concerns (41.7%), and increased healthcare costs (41.7%). Although most participants reported using AI in daily life (68.8%) and noted that AI made the completion of tasks easier (62.5%), most have not incorporated AI into their clinical practice (62.5%), and felt that inadequately trained or equipped to do so (79.2% and 58.3% respectively).ConclusionOMS specialists and trainees in Singapore generally have optimistic views toward AI, with younger respondents tending towards more positive attitudes. The levels of knowledge and practice leave room for improvement.